An Analysis of Idiomatic Expressions used in the Book of Rich Dad Poor Dad - Arsiwela Arsiwela; Tegar Arif Topan; Idha Dwi Permatasari; Hana Fauziah (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study investigated the idiomatic expressions used in Rich Dad Poor Dad book. The main goals were to find out what these idioms mean, what makes them unique, and how they can help in learning English. The researchers found and analyzed 30 idioms. This study used a qualitative approach. The data came from the idiomatic expressions that were used in the book of Rich Dad Poor Dad. The process had three steps: organizing the data, choosing which idioms to focus on, and carefully reading through them. The researchers used Adam Makkai's theory to classify the idioms. According to this theory, idioms can be either lexemic or sememic. In this study, all the idioms were lexemic. There are five types of lexemic idioms: phrasal verb idioms, tournure idioms, irreversible binomial idioms, phrasal compound idioms, and integrating verb idioms. The study found 2 incorporating idioms, 8 phrasal compound idioms, 1 irreversible binomial idiom, 13 tournure idioms, and 6 phrasal verb idioms.